EFFECTS OF SOCIO-CULTURAL ONLINE TRENDS ON ADOPTION OF DIGITAL MARKETING AMONG UNIVERSITIES IN KENYA - Obwatho, Simon, Thuo, John Kuria, Mwiti, Evans (International Journal of Research Science and Management, 2015)
Over thousands of years, buying and selling has been conducted using the available tools and technologies. Such technologies and tools have been evolving over the many years. Today, the customer is rapidly changing in terms of behavior and needs. The objective of this study was to establish the effects of socio-cultural online trends on adoption of digital marketing among universities in Kenya. Many studies have been done on digital marketing and on most of the factors influencing adoption of digital marketing: Also studies have been done on socio-cultural online trends. However, there is a substantial gap in studies seeking to test the causation between socio-cultural online trends and adoption of digital marketing. There is a substantial gap in studies seeking to test the causation between economic trends and adoption of digital marketing. The methodology and philosophy of this study is guided by logical Positivism. This research therefore adopted a combination of correlational and descriptive. Findings indicated that internet communication, linguistic tools and styles and mobile and online language oblige respondents to engage in digital marketing. However, there was a week agreement to the insinuation that there are enough individual and organizational social actors to drive the digital marketing agenda among universities.